Thermo-mechanical analysis of mass concrete foundation slabs at early age - essential aspects and experiences from the FE modelling - Smolana, Aneta (2022)
In this paper, the focus is placed on essential aspects of finite element modelling of thermo-mechanical behaviour of massive foundation slabs at early ages. Basic decision-making issues are discussed in this work: the potential need to explicitly consider the casting process in the modelling, the necessary size of the underlying soil to be modelled and the size of the FE mesh, and the need of considering daily changes of the environmental temperature and the temperature distribution over the depth of the soil. Next, the contribution of shrinkage to early age stresses, the role of the reinforcement, and the type of mechanical model are investigated. Comparative analyses aiming to investigate the most important aspects of the FE model and some possible simplifications with negligible effect on the results are made on the example of a massive foundation slab. Finally, the results are summarized with recommendations for creating the FE models of massive slabs at early ages.